The multinational enterprise, capabilities, and digitalization: governance and growth with world disorder - Teece, David J. (Journal of international business studies, 2025)
This essay revisits my 2014 JIBS article about the potential for integrating international business internalization theory with a strategic management capabilities perspective. It recaps the capabilities framework with an emphasis on the learning required of emerging market multinationals and illustrates this with the case of Hyundai Motor Company’s internationalization and growth. It also discusses two aspects of the global economy that have become more prominent since 2014 in shaping international business: geopolitical uncertainty and digitalization. A rise in geopolitical tensions appears to be rebalancing the relationships between multinationals and home/host governments. Digitalization facilitates international business; but it adds new vulnerabilities by (further) accelerating competition, enabling new rivals, and introducing systemic risks into digital supply chains. Implications for managers, board members, and international business scholars are drawn.